Relationship between betatrophin levels and metabolic parameters in patients with polycystic ovary syndrome - Erbag, G; Eroglu, M; Turkon, H; Sen, H; Binnetoglu, E; Aylanc, N; Asik, M (Cellular and Molecular Biology, 2016)
To evaluate the status of serum betatrophin levels and potential relations between metabolic parameters and betatrophin levels in patients with polycystic ovary syndrome. We included patients newly diagnosed with PCOS in our study. Fifty-seven female patients (30 patients with PCOS and 27 healthy control subjects) were enrolled in this study. Serum betatrophin levels were measured using a betatrophin enzyme-linked immunosorbent assay kit. Insulin resistance was calculated using the homeostasis model of the assessment-insulin resistance index formula. The betatrophin level was 1538,85 ng/L in the patient group and 2440,46 ng/L in the control group, and the difference was statistically significant (p=0.003). A significantly negative correlation was found between betatrophin level and insulin, HOMA-IR, and BMI. Betatrophin levels in patients with PCOS are lower than those without PCOS and inversely related to insulin resistance.